Edukasi tentang Remaja Percaya Diri dan Latihan Emotional Freedom Technique (EFT) dalam Upaya Peningkatan Harga Diri Remaja - Fajriyati Nur Azizah; Sar, Alfie Ardiana; Pamungkas, Dewi Retno (The Journal of Innovation in Community Empowerment, 2024)
Adolescence is a time of identity formation. If this phase is skipped, it can result in a negative self-concept, distorted self-image, slow self-development, low self-esteem, identity shifts, and even role confusion. Adolescents who are able to overcome challenges, pay attention to the world around them, and participate in social interactions will have a positive self-concept. The method of implementing this community service activity is by conducting adolescent mental health education and training to increase adolescent self-confidence with the EFT Technique. Activities are carried out for 1 month. The steps of Community Service activities consist of three stages, namely the preparation stage, the implementation stage, and the final stage. most students are 11 years old (53%), male (57%) and are in grade VI (63%). The results of the activities carried out can be seen an increase in the aspects measured, namely student confidence measured using Rosenberg's modified self-confidence questionnaire, and other abilities that can be observed, namely the ability to do EFT, the ability to mention and show their respective strengths in front of the group, and the ability to write at least 5 student strengths on folding paper. The self-confidence table shows an increase in student self-confidence between before and after a series of activities to increase self-confidence. The mean score of self-confidence increased by 2 points from 30.27 to 32.33. The minimum value of self-confidence level has increased from 25 to 28. Meanwhile, the maximum value of self-confidence has also increased from 35 to 37 points. The value range of adolescent self-confidence is between 10-40 points. The higher the value or score of students' self-confidence, the higher their self-confidence, and vice versa. The study results show that providing education about self-confidence, EFT and games aimed at increasing self-confidence can increase the average student self-confidence score.